Frontex and the convergence of humanitarianism, human rights and security. (December 2018) - Perkowski, Nina
While there has been growing scholarly interest in the convergence of humanitarianism and security in contemporary EUropean border governance, much of the existing literature has neglected the role of human rights in this process. Drawing on in-depth interviews with Frontex officials, this article takes the simultaneous portrayal of the agency as rescuer of migrants at sea, promoter of fundamental rights and defender of EUropean citizens against migrant threats as a starting point to rethink the relationship of humanitarianism, human rights and security in the governing of EUropean borders. Conceptualizing them as discourses of protection that render their subjects vulnerable in various ways, the article contributes to a deeper understanding of the connections and combined effects of humanitarianism, human rights and security in EUropean border governance. Finally, it shows that Frontex's positioning in humanitarian, human rights and security terms has strengthened the agency in three ways. First, it has allowed Frontex to cooperate with a range of actors in 'managing' EUropean borders. Second, it has enabled the agency to become a 'go-to' solution to diverse crises in border governance. Third, it has allowed Frontex officials to shift blame for human rights abuses to member-states.